Systematic joints in sandstone - Wojtal, Steven F. (Oberlin College Library, 1986)
Two sets of systematic joints (or fractures with no visible offset) cut this inclined sandstone layer, producing a regular pattern of rectangular blocks of sandstone. The joints with traces that are nearly parallel to the strike of the bed abut against the laterally continuous joints with traces essentially parallel to the dip of the sandstone, indicating that the joints with strike-parallel traces are younger than those with dip-parallel traces.